Study of antimicrobial activity of fermented coconut water with different solvent against bacterial leaf blight of rice (Oryza sativa) / Amar Shahrizat Akim - Akim, Amar Shahrizat (Faculty of Plantation and Agrotechnology, 2018)
In Malaysia, rice (oryza sativa) is the most important food crop that must be protect and preserve because the population in this country main rely of rice as their food sources. Threat to rice crop are mostly come from pest and diseases in which the most prominent is the bacterial leaf blight cause by the bacteria xanthomonas oryzae. This in-vivo study was observed and recorded the antimicrobial activity of fermented coconut water extract with different solvent against bacterial leaf blight of rice. Two type of paddy variety is used. Two recent Malaysia rice varieties namely MR 253 and MR 297 were used in this experiment. Mature fermented coconut water that has antibacterial activity and may be used as biological control against plant pathogens. The antibacterial activities from coconut water that has been fermented and extracted with solvent of methanol and distilled water can be used against Xanthomonas oryzae causal agent of bacterial leaf blight for paddy (Oryza sativa). These two extract were obtained from methanol and aqueous and used as treatments for the inoculated paddy of two varieties which are MR253 and MR 297 with Xanthomonas oryzae in this study. There are many methods to control bacterial blight disease either by chemical, physical control or cultural control. However the purpose of this study is to help paddy grower to develop of a new way to control using Xanthomonas oryzae. The objective of this study is to screen the potential of antimicrobial activity of fermented mature coconut water extracted with different solvent against Xanthomonas oryzae in vivo and to evaluate the response of different paddy variety inoculated with bacterial leaf blight.